Analisis Faktor-Faktor yang Mempengaruhi Persepsi Jurnalis Televisi terhadap Perkembangan Bank Syariah Di Indonesia - Rizki Amelia; Didin Hafidhuddin; Hendri Tanjung (AL-MUZARA'AH, 2014)
Indonesia is the largest Moslem population in Southeast Asia (CIA, 2013), but Islamic banking market share in Indonesia is still low (BI,2014). This condition happened because Islamic banking information was not well accepted in the society. Television journalist has important role in spreading this information. The purpose of this study was to analyze perception and factors that build television journalist perception in Islamic banking news making. This study used theory of planned behavior (TPB) and structured equation modeling (SEM) to assess television journalist perception in Indonesia’s Islamic banking development. The assessment evaluated intention and ability to explain their intention in subjectivenorm (SN), attitude toward behavior (ATB), and perceived behavior control (PBC). The result showed that SN, ATB, and PBC were positively influence television journalist perception on Islamic banking development in Indonesia. SN and PBC were positively influence journalist intention to make Islamic banking news.